Kinematic design of a new parallel kinematic machine for aircraft wing assembly - Yan Jin; Xianwen Kong; Higgins, C.; Price, M. (IEEE 10th International Conference on Industrial Informatics, 2012)
PKM (parallel kinematic machine) based production systems have shown their potential for large volume manufacturing. However, integrating 5-axis PKM machine tools directly into an existing system will lead to unnecessary redundant motions, which may cause many negative effects on the accuracy and productivity of the system. To cope with this problem, a new PKM based production system for aircraft wing assembly, named PAW, is proposed by using a holistic design approach in this paper. PAW is constructed by a unique PKM architecture mounted on a gantry-like worktable. Mobility, kinematics and Jacobian analyses are conducted, as well as dimensional optimization for the new PKM. Specially, the task space variables are directly employed for kinematic analysis, and the task workspace is directly utilized for the dimensional synthesis. As a result, the PAW system shows a better performance comparing to the those currently in production. It is not only suitable for wing assembly tasks (e.g. drilling) but also for other large volume manufacturing tasks, such as trimming and sealing.